Studi Literatur Manajemen dan Risiko Kepatuhan pada Bank Syariah - Dzulham Fadillah; Dinar Rahmayanti; Iqlima Fairuz Syifa (Jurnal Manajemen, 2020)
One of the risks faced by Islamic banks is compliance risk. The study was conducted to determine efforts to manage Islamic banks compliance risk is good. The research method uses the study of literature, namely the process of data collection is done through literature studies sourced from books, the internet and journals relating to the themes discussed. The results obtained by Islamic banks need to prepare work units and policies and clear compliance procedures, followed by the process of identifying, mitigating and controlling compliance risk and evaluating the achievement of efforts that have been made.